2020
DOI: 10.1002/acp.3703
|View full text |Cite
|
Sign up to set email alerts
|

The impact of evidence lineups on fingerprint expert decisions

Abstract: Summary Forensic examiners routinely compare a crime‐relevant mark of unknown origin against a single suspect's sample, which may create an expectation that the two will match. We tested how embedding the suspect's sample among known‐innocent fillers (i.e., an evidence lineup) affects expert decision‐making. Experienced fingerprint examiners (N = 43) compared crime‐relevant marks against either individual suspect fingerprints (i.e., the standard procedure) or arrays of fingerprints (i.e., evidence lineups), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Ribeiro et al (2019) also found that jurors underestimated fingerprint examiners' accuracy (88%) relative to their actual accuracy rates in proficiency studies (97%; Tangen et al, 2011;Ulery et al, 2011). Thus, jurors may sometimes overvalue and sometimes undervalue forensic evidence-but importantly, for any forensic discipline whose error rate is unknown (NAS, 2009; see also Dror, 2020b), it is impossible to know if jurors are giving the evidence too much or too little weight.…”
Section: Jurors' U Nderstandingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribeiro et al (2019) also found that jurors underestimated fingerprint examiners' accuracy (88%) relative to their actual accuracy rates in proficiency studies (97%; Tangen et al, 2011;Ulery et al, 2011). Thus, jurors may sometimes overvalue and sometimes undervalue forensic evidence-but importantly, for any forensic discipline whose error rate is unknown (NAS, 2009; see also Dror, 2020b), it is impossible to know if jurors are giving the evidence too much or too little weight.…”
Section: Jurors' U Nderstandingmentioning
confidence: 99%
“…As it stands, many laboratories either create and distribute their own proficiency tests or they contract an external organization to do so. However, scholars have noted that proficiency test results are only informative to the extent that the tests approximate actual casework (e.g., Dror, 2020b;Koehler, 2013;Mejia et al, 2020;Risinger et al, 2002)-and unfortunately, proficiency tests often fall short in two important respects.…”
Section: B Lind P Roficiency Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results have shown that examiners made a positive identification of 37.8% for displayed images; by contrast, 25.6% images were classified as inconclusive. The main drawback of [29] is that examiners were aware of being part of a monitored study. This may explain why the study output an unusually high rate of inconclusive judgments attributed to suspicion of examiners aware they were under assessment.…”
Section: Research On the Performance Of Experts In Latent Fingerprint...mentioning
confidence: 99%
“…The analysis of these errors is critical to understand the performance of these systems. There are studies analyzing the likelihood of human errors in the stages a to c and showing these errors are habitual [26][27][28][29]. Nevertheless, there are not studies evaluating how these errors affect the identification stage, (d).…”
Section: Introductionmentioning
confidence: 99%